ACTUAL PROBLEMS OF FUNCTIONING CAPACITY OF THE NATIONAL ECONOMIC SYSTEM - Boris Kallagov; Madina Tsutsieva; Zalina Tedeeva (Вестник Северо-Кавказского федерального университета, 2022)
In present article is analyzed the condition of economical processes in modern national economic system in clauses of transitional period. While looking through the formed modern Russian model of market economy geopolitical role of government is designated subject. In social and cultural context Russia appears to be a connecting link between eastern and western civilazations. It is noticed that Russian society in economical context historically formed in western type but at the same time it saved its own not alike with the overs features in economical traditions and activity. Essential problems of modern society's condition of economic were identified and the line of offers to improve the methods of controling economical prosesses, adequate the dynamics of transitional period, was introdused.